Hepatitis B virus surface antigen and anti‐hepatitis C virus rapid tests underestimate hepatitis prevalence among HIV‐infected patients. Issue 9 (9th April 2014) - Hønge, BL; Jespersen, S; Medina, C; Té, DS; da Silva, ZJ; Østergaard, L; Laursen, AL; Wejse, C; Krarup, H; Erikstrup, C; Bissau HIV cohort study group
<x xml:space="preserve">Abstract</x> Objectives In the case of coinfection with HIV and hepatitis B virus (HBV) and/or hepatitis C virus (HCV), hepatic disease progression is often accelerated, with higher rates of liver cirrhosis and liver‐related mortality. We aimed to evaluate the performance of the rapid tests used routinely to detect HBV surface antigen (HBsAg) and anti‐HCV among HIV‐infected patients in Guinea‐Bissau. Methods Blood samples from HIV‐infected patients in Guinea‐Bissau were stored after testing for HBsAg and anti‐HCV with rapid tests. Samples were subsequently re‐tested for HBsAg and anti‐HCV in Denmark. Results Two rapid tests were used in Guinea‐Bissau: HBsAg Strip Ref 2034 (VEDA.LAB, Alençon, France; sensitivity 62.3%; specificity 99.2%) and HEPA‐SCAN (Bhat Bio‐Tech, Bangalore, India; sensitivity 57.1%; specificity 99.7%). In the two tests the ability to obtain the correct outcome depended on the antigen and antibody concentrations, respectively. Sex, age, CD4 cell count and antiretroviral therapy status did not differ between false negative and true positive samples in either of the tests. The study is limited by a low number of anti‐HCV positive samples. Conclusions New diagnostic rapid tests should always be evaluated in the setting in which they will be used before implementation.